Copper in N-heterocyclic chemistry - Srivastava, Ananya (Elsevier, 2020)
Copper in N-Heterocyclic Chemistry provides an overview of copper-catalyzed synthesis and functionalization of N-heterocyclic compounds, covering all recent developments in a way that is ideal for researchers and students working in the area of synthetic organic chemistry and medicinal chemistry. The book explores N-heterocyclic compounds as unique structural units in the development of natural products and pharmaceuticals, along with the remarkable progress made in the area of high atom economic strategies, and more recently, copper-catalyzed C-H activation and its applications in organic synthesis. Readers will find troubleshooting protocols, as well as the advantages and limitations of each method discussed. As copper catalysts show versatile chemical reactivity in many aspects, including their oxidation states 0-3 are accessible and their ability to facilitate bond formations due to their ability to serve as Lewis acids, oxidizing agents and catalysts, this book is an ideal resource on the topics explored.